Simulation and optimization of anaerobic co-digestion of food waste with palm oil mill effluent for biogas production - Tiong, J.S.M. (MDPI, 2021)
Food waste (FW) utilized as substrate for anaerobic digestion (AD) to produce biogas is promising. Simultaneously, waste is handled and value-added products such as biogas and fertilizer are produced. Palm oil mill effluent (POME) is used as the co-substrate. This study aims to simulate the complete process flow of anaerobic co-digestion (AcoD), consisting of pre-treatment of feedstock, biogas upgrading, wastewater treatment and sludge dying using SuperPro Designer. Parameters, namely hydraulic retention time (HRT), recycle ratio of sludge, water to FW ratio (kg/kg) and co-substrate to FW ratio (kg/kg), would affect the performance of digester. The optimization of these parameters is performed using Design-Expert software, involving response surface methodology (RSM). The effects on responses such as methane flow, chemical oxygen demand (COD) and volatile solid (VS) removal efficiencies are analyzed. In treating 25,000 kg/h of feed, the optimized values for HRT, recycle ratio, water to feedstock ratio, POME to FW ratio are 37.2 days, 0.381, 0.027 and 0.004, respectively. The methane yield is 0.30 L CH4/g of COD removed, with COD and VS removal efficiencies of 81.5 and 68.9, respectively. The project is profitable, with a payback period of 6.14 years and net present value (NPV) of 5,680,000. A comprehensive understanding of AD matures it for commercialization purposes. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.